Emergence of Large-Scale Magnetic-Vortices Structures by Small-Scale Helicity in Stratified Magnetized Plasma - Kopp, Michael I.; Yanovsky, Volodymyr V. (East European Journal of Physics, 2025)
In this paper, a new type of instability is identified, leading to the generation of vortex motions and magnetic fields in a plasma layer with a constant temperature gradient, subjected to uniform gravity and a vertical magnetic field. The analysis in this study is conducted within the framework of electron magnetohydrodynamics (EMHD), taking into account thermomagnetic effects. A new large-scale instability of the α-effect type is identified, which facilitates the generation of large-scale vortex and magnetic fields. This instability arises due to the combined action of an external uniform magnetic field, oriented perpendicular to the plasma layer, and a small-scale helical force. The external force is modeled as a source of small-scale oscillations in the electron velocity field, characterized by a low Reynolds number (R<<1). The presence of a small parameter in the system allows for the application of the method of multiscale asymptotic expansions, leading to the derivation of nonlinear equations governing the evolution of large-scale vortex and magnetic perturbations. These equations are obtained at third order in the Reynolds number. A new effect associated with the influence of thermal forces (the Nernst effect) on large-scale instability is also discussed. It is shown that an increase in the Nernst parameter reduces the α-coefficient and thereby suppresses the development of the large-scale instability. Using numerical analysis, stationary solutions of the vortex and magnetic dynamo equations are obtained in the form of localized helical-type structures.